2019
DOI: 10.14311/nnw.2019.29.016
|View full text |Cite
|
Sign up to set email alerts
|

Improved Antlion Optimizer Algorithm and Its Performance on Neuro Fuzzy Inference System

Abstract: Antlion optimizer algorithm (ALO) is inspired by hunting strategy of antlions. In this study, an improved antlion optimization algorithm is proposed for training parameters of adaptive neuro fuzzy inference system (ANFIS). In the standard ALO algorithm, the greatest deficiency is its long running time during optimization process. The random walking model of ants, the selection procedure and boundary checking mechanism have been developed to speed up standard ALO algorithm. To evaluate the performance of the im… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 27 publications
0
6
0
Order By: Relevance
“…IALO result has the second best cost value as -1078209.911. In the results of all algorithms, facility pairs (19)(20), (11)(12)(13)(14)(15)(16) For QAP, the comparison results with 10 independent runs of IALO and the others are given in Table 7. This consists of mean cost, standard deviation, best cost and worst cost values from 10 runs.…”
Section: Qap Test Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…IALO result has the second best cost value as -1078209.911. In the results of all algorithms, facility pairs (19)(20), (11)(12)(13)(14)(15)(16) For QAP, the comparison results with 10 independent runs of IALO and the others are given in Table 7. This consists of mean cost, standard deviation, best cost and worst cost values from 10 runs.…”
Section: Qap Test Resultsmentioning
confidence: 99%
“…There are some studies reported in the literature regarding applications or improvement of the ALO algorithm. Some of these are: PID controller parameters design [2], optimal non-convex and dynamic economic load [3], tournament selection based ALO algorithm for solving parallel machine scheduling [4] and quadratic assignment problem [5], optimal flexible process planning [6], optimal route planning for unmanned aerial vehicle [7], multi objective optimal generation scheduling [8], automatic generation control of interconnected power system [9], determining the optimal coefficients of IIR filters [10], and optimization of parameters on neuro-fuzzy inference system [11], [12].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…They are still at the evolving stage and suffer from some problem. For example, the ant lion algorithm suffers from long run time, local optima stagnation 24,25 . Grey‐wolf algorithm has low solving accuracy and bad local searching ability.…”
Section: Proposed Workmentioning
confidence: 99%
“…In [120] Yu proposed an improved version of antlion by hybridizing ALO with Nelder-Mead algorithm and apply it to detect structural damage by improving weighted trace lasso regularization. Kilic et al [121] introduced IALO algorithm by using the absolute value of fitness value before applying roulette wheel selection. In addition to the above enhancement, Zhang et al in [122] showed another improved approach of ALO by integrating it chaotic mapping theory with initialization and random walk process.…”
Section: ) Improved Alomentioning
confidence: 99%